1998
DOI: 10.1074/jbc.273.12.6736
|View full text |Cite
|
Sign up to set email alerts
|

Type I cAMP-dependent Protein Kinase Delays Apoptosis in Human Neutrophils at a Site Upstream of Caspase-3

Abstract: Current data suggest that apoptosis controls neutrophil numbers in tissues. We analyzed roles for and the sites of action for the cAMP-dependent protein kinases (cAPKs) in apoptosis induced in human neutrophils by in vitro storage, cycloheximide (CHX) exposure, and anti-Fas exposure. Treatment with 8-chlorophenylthiocAMP (8-CPT-cAMP) prolonged the time required for 50% of the cells to exhibit apoptotic morphology (t 50 ) from 16.3 to 41.8 h (in vitro culture), from 2.4 to 7.8 h (CHX), and from 4.8 to 6.5 h (an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 39 publications
9
92
0
Order By: Relevance
“…Melanomas were dissected out of the mouse and frozen in liquid nitrogen. Extracts were prepared from thawed tissue homogenates and assayed for caspase activity using the fluorogenic substrate Ac-DEVD-AFC (Alexis Biochemicals, San Diego, CA) as previously described [20]. This peptide sequence is based on the PARP cleavage site, Asp 216 , for caspases 1, 3, 4, and 7, that exhibits enhanced fluorescence upon cleavage.…”
Section: Determination Of Caspase Activation In Vitromentioning
confidence: 99%
“…Melanomas were dissected out of the mouse and frozen in liquid nitrogen. Extracts were prepared from thawed tissue homogenates and assayed for caspase activity using the fluorogenic substrate Ac-DEVD-AFC (Alexis Biochemicals, San Diego, CA) as previously described [20]. This peptide sequence is based on the PARP cleavage site, Asp 216 , for caspases 1, 3, 4, and 7, that exhibits enhanced fluorescence upon cleavage.…”
Section: Determination Of Caspase Activation In Vitromentioning
confidence: 99%
“…cAMP, however, was also reported to inhibit PI3-K-induced activation of p70S6 kinase in IL-2-responsive cells (63). Specific cell context may be important in the function of PDE3B and cAMP in the action of PKB on cell proliferation/survival, since, in some cells, cAMP actually promotes growth (48,64) and prevents or delays apoptosis (65).…”
Section: Effects Of Pde Inhibitors and Camp On Bad Phosphorylation Anmentioning
confidence: 99%
“…cAMP has also been reported to inhibit apoptosis upstream of caspase 3 activation in human neutrophils. 231 Several studies have shown that PKA activation results in the phosphorylation of Bad on serine residue 112. 232 This is the same site that is phosphorylated by Raf-1 and Mek and may represent the site upstream of caspase 3 activation that is inhibited by PKA.…”
Section: Pkamentioning
confidence: 99%